Editorial (Journal of Decolonising Disciplines, 2021)
In July 2019, the University of Pretoria, in association with Wits, UFS, Rhodes, UKZN, UWC, Stellenbosch University and UCT, its partners inthe Mellon programme titled ‘Unsettling paradigms: The decolonial turn in the Humanities curriculum at universities in South Africa’,hosted a conference on the theme ‘The decolonial turn and the humanities: Prospects, practice and interventions’. A number of papers were subsequently reworked as articles and submitted for peer review with a view to their publication in this second issue of the first volume of the Journal of Decolonisng Disciplines (JDD). The six articles selected for publication speak to some of the broad themes of the conference, butwhat binds them together is their shared focus on pedagogy, practice and interventions—some of the core issues underlying the quest for the decolonisation of the humanities curriculum.
Keywords: decolonisation; Humanities Curriculum; Unsettling Paradigms; decolonial turn